2019
DOI: 10.1039/c9cp02844g
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying electronic similarities between NHC–gold(i) complexes and their isolobal imidazolium precursors

Abstract: The σ and π donor/acceptor properties of the carbon–gold bond are manifested by changes in 197Au spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In this sense, Belpassi and Zuccaccia examined the σ donation and the π back-donation in Au­(NHC)-based complexes, taking into account the trans ligand to the NHC, continuing the work of Ciancaleoni and Belpassi in the same sense, although the latter only considered the use of phosphine ligands . More recently, the π back-donation has been analyzed to distinguish between cationic Au-NHC complexes and their isolobal NHC-proton compounds . However, for the case of Grubbs olefin metathesis catalysts, in order to properly define the NHC ligand, its description should be in combination with, at least, the trans Ru–P bond.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Belpassi and Zuccaccia examined the σ donation and the π back-donation in Au­(NHC)-based complexes, taking into account the trans ligand to the NHC, continuing the work of Ciancaleoni and Belpassi in the same sense, although the latter only considered the use of phosphine ligands . More recently, the π back-donation has been analyzed to distinguish between cationic Au-NHC complexes and their isolobal NHC-proton compounds . However, for the case of Grubbs olefin metathesis catalysts, in order to properly define the NHC ligand, its description should be in combination with, at least, the trans Ru–P bond.…”
Section: Introductionmentioning
confidence: 99%
“…However, differences are scarcer than expected. In particular, IMes and SIMes ligands are thermodynamically more stable than IMe by 0.73 kcal mol –1 and 1.10 kcal mol –1 , respectively, which, at the same time would be more stable than the larger IPr and IPr* ligands, but by less than 1 kcal mol –1 . Kinetically, the energy barriers range from 9.55 kcal mol –1 for IMe to 12.91 kcal mol –1 , not for IPr*, but for IPr.…”
Section: Resultsmentioning
confidence: 98%
“…This study was extended with [(NHC)PPh] adducts and it was shown that the 31 P NMR chemical shift only qualitatively correlates with the π acceptor properties of the NHCs . A recent computational study of various [(NHC)AuCl] complexes focused on Au NMR found a correlation between the π‐accepting ability of these complexes and the 197 Au chemical shift . Furthermore, they also found that the paramagnetic shielding tensor of the carbene‐C atom is the main shielding term which shows variation by changes in the (NHC) moiety.…”
Section: Introductionmentioning
confidence: 94%